INTERNATIONAL EXPERIENCE WITH IFRS AND ITS IMPLEMENTATION IN UZBEKISTAN - Kilicheva Farida Beshimovna; Imamova Nasiba Muzafarovna; Mirsadikova Dilobar Dilshod qizi (Scholar Express Journals, 2022)
This article discusses the organization of accounting and reporting systems in business entities based on international financial reporting standards. Attention is focused on the fact that the introduction of international financial reporting standards will provide users with internal and external information, information about the financial condition of the enterprise, improve the management system of economic entities, increase the competitiveness of the enterprise, improve comparability of indicators, expand opportunities for analyzing its activities, facilitate access to international capital markets.
Keywords: Financial Results; Risks; Shareholders; Employees